Frictional drag on surfboard fins - Tee, Nicholas Kong Hui (2018)
With wave surfing gaining popularity over the past decade, it is imperative to enhance the performance of the surfer for better ridability. The key to performance lies in the fin of the surfboard. Surfboard fins are hydrofoils attached at the tail-end of the surfboard to augment control and directional stability through foot steering. They have many different characteristics and various fin configurations which play an integral role in determining the speed, manoeuvrability, stability, control and the overall performance of the surfboard. Past research in this field were few and far between and the hydrodynamic performance of surfboard fins were mainly obtained with the help of Computational Fluid Dynamics. Hence, there is a need to validate some of the CFD data obtained to see if there are any correlations. One such validation method involves the usage of a wind tunnel to obtain drag performance data. The primary objective of this project was to conceptualise a methodology to measure drag forces on surfboard fins in a wind tunnel that was representative of actual conditions. Two fins, from a fin company named Futures, were used. One was a normal fin while the other was a 3-D dimpled fin. These fins were then tested under varying speeds and angles of attack in a closed loop wind tunnel. Two experimental setups were created, one of which utilised the internally mounted six-component force balance to measure drag data while the other utilised an external load cell which measures tension and compression forces. Lift forces were not analysed due to insufficient data available for comparison. The drag force exhibited a positive correlation to increasing magnitudes of speed and angle of attack. The 3-D dimpled fin also experienced lower drag force at a smaller speed range as compared to the normal fin. Lastly, the report covers future recommendations which are to be followed up upon from this project in order to further comprehend the hydrodynamic performance of the surfboard fin in a wind tunnel.